GOOD CORPORATE GOVERNANCE ARRANGEMENTS IN STATE-OWNED PALM COMPANIES PRIVATE COMPANIES IN INDONESIA - Junaedi , Junaedi (International Journal of Social Science, 2024)
The concept of GCG has long been known in developed countries, such as Europe and America, with the separation between capital owners and company managers. This concept became hot in America in the eighties when takeover scandals and share sale scandals to management buyouts emerged which worried shareholders. In this case, the company management who was mandated by shareholders did not manage the company well. There is abuse of authority by management for personal interests without considering the interests of shareholders. "Seeing these situations and conditions, activists and observers of corporate issues have begun to formulate a system so that company managers are accountable (accountable) to shareholders and parties related to company activities (stakeholders). The use of good governance principles in the business world is called Good Corporate Governance (GCG). In other words, the business world must also build and maintain GCG principles, namely: participation, laws and regulations, transparency, responsiveness, consensus orientation, justice and fairness, efficiency and effectiveness, accountability and strategic vision. BUMN is constitutionally recognized as playing a very important role in the national economy, alongside the private sector and cooperatives. In the national economic system, BUMN plays a role in producing the goods and services needed to realize the greatest prosperity of the people. The role of BUMN is felt to be increasingly important as pioneers or trailblazers in business sectors that are not yet of interest to the private business sector. BUMN also has a strategic role in implementing public services, balancing the power of the large private sector and helping to develop small businesses and cooperatives. BUMN is also a significant source of state revenue in the form of various types of taxes, dividends and privatization proceeds.The GCG principles that must be implemented by BUMN based on the BUMN Ministerial Decree, consist of the principles: Transparency, Independence, Accountability, Fairness. Other provinces that are classified as the largest national palm oil producers are Central Kalimantan, North Sumatra, West Kalimantan and South Sumatra.Then the smallest palm oil production is in Kep. Riau, North Maluku, Maluku Gorontalo, Banten and West Java.Meanwhile, provinces that do not have palm oil production are DKI Jakarta, Central Java, DI Yogyakarta, East Java, Bali, West Nusa Tenggara, East Nusa Tenggara and North Sulawesi, as shown in the graph. India will be the country with the highest export value in 2022, reaching US$5.32 billion. The volume of exports to this country was also recorded as the largest, namely 4.99 million tons in the same period